general geometric formula is
![A_n=A_1\cdot r^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/thx7nqlnuruboox91m9es11xul5buakqrg.png)
then we replace using A3
![\begin{gathered} A_3=A_1\cdot r^(3-1) \\ \\ (16)/(3)=A_1\cdot r^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/it605ml4k7obun0viykd6smofo8d35wbtp.png)
now replace using A5
![\begin{gathered} A_5=A_1\cdot r^(5-1) \\ \\ (64)/(21)=A_1\cdot r^4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9bjuaoy90wflu045hl0koki22i6wpm9fdl.png)
now we have two equations and two unknow
![\begin{gathered} (16)/(3)=A_1\cdot r^2 \\ \\ (64)/(21)=A_1\cdot r^4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wz8isuyhq1b6jxh2xcar1z8856dywzkks1.png)
we can solve A1 or r from any equation and replace on the other
I will solve A1 from the first equation
![A_1=((16)/(3))/(r^2)](https://img.qammunity.org/2023/formulas/mathematics/college/173bfjvl5y3x7x6gyjr4jbbq27oxfo45p1.png)
and replace on the second to solve r
![\begin{gathered} (64)/(21)=(((16)/(3))/(r^2))\cdot r^4 \\ \\ (64)/(21)=(16)/(3)\cdot r^2 \\ \\ r^2=(64*3)/(21*16) \\ \\ r^2=(192)/(336)=(4)/(7) \\ \\ r=\frac{2\sqrt[]{7}}{7} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y1btuujcl5odbhlnu236y8m73b790ujuxc.png)
now replace r on the other equation to find A1
![\begin{gathered} (16)/(3)=A_1\cdot(\frac{2\sqrt[]{7}}{7})^2 \\ \\ (16)/(3)=A_1\cdot(4)/(7) \\ \\ A_1=(16*7)/(4*3) \\ \\ A_1=(28)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/emmzl1s5qdccgnheuc01s3aqjf7v70jpji.png)
now we have the two unknows A1 and r then replace on the general geometric equation
![A_n=(28)/(3)\cdot(\frac{2\sqrt[]{7}}{7})^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/518wz1ntm52l6vzyd081davc6alglhoh0p.png)